Juridic Consideration of The Judgment's Decision Concerning the Post-Born of Children Born Out of Marriage After Decision of The Constitutional Court Number 46 / PUU-VIII/ 2010 - Edi Hudiata (International Journal of Nusantara Islam, 2021)
Marriage law in Indonesia stipulates that a legal marriage is a marriage that is carried out according to the teachings or provisions of their respective religions and is registered by the relevant government agency authorized to do so. With a registered marriage, the state recognizes all the rights and obligations attached to each married couple which is protected by existing legal instruments. The principle of judge freedom is part of the judicial authority. namely the power of an independent state to administer justice to uphold law and justice. The principle of freedom of judges in carrying out their duties as judges can provide an understanding that judges in carrying out the duties of judicial power may not be bound by anything and/or pressured by anyone, but are free to do anything. The principle of freedom of judges is independence or independence possessed by a judicial institution for the sake of creating an objective and impartial decision.